Natural compounds as mosquito larvicides: A comprehensive review - Anamika, KS; Manikantan, Pappuswamy (Plant Science Today, 2025)
As a tropical country, India is a fertile breeding ground for mosquitoes, leading to more than 7 lakh deaths annually. The need to control their widespread use was essential globally, leading to chemical usage. Synthetic insecticides used in chemical control methods have been preferred since the previous era due to their spontaneous effect and ease of application. However, it has now been recognized that chemical insecticides and larvicides cannot be utilized for vector control on the same scale due to many known and unknown causes. The problems, ranging from general skin irritation to severe deadly issues such as genetic disorders, have been reported. The mosquito population is increasing daily due to many factors, such as environmental pollution, water quality, global warming, and so on, which are causing detrimental effects; however, these are interconnected, which worsens the scenario. Even though undeveloped countries suffer from those mentioned above, cost-effective eradication is a topic to be interrogated. Hence, they follow and use cheap chemicals common in the market, leading to environmental pollution. Therefore, it is necessary to investigate the possible efficacy of biologically active plant extracts to lessen pollution and lower expenditure. This review examines 30 plants from 10 families, highlighting their effects on mosquito larvae and potential use in controlling mosquito populations.